Evaluation of the treatment efficacy of titanium elastic nail in addition to external fixator in humeral diaphyseal fractures: Comparison of three treatment methods (Annals of Medical Research, 2022)
Aim: This study aimed to compare the clinical and radiological outcomes of combined titanium elastic nailing and external fixator application (TEN+EFA) with EFA and plate osteosynthesis in patients with humerus diaphysis fractures.Materials and Methods: Data of the patients who underwent surgical treatment for a humerus diaphysis fracture were retrospectively reviewed. The patients were divided into three groups based on the surgical technique. Group 1 consisted of the patients who underwent plate osteosynthesis, Group 2 included those who underwent EFA, and Group 3 included those who went through TEN+EFA. Results: Eighty patients were included. The number of patients in the study groups was 32, 25, and 23 in Group 1, 2, 3, respectively. The duration of surgery was statistically significantly shorter in Groups 2 and 3 than in Group 1 (p=0.02). Nonunion was diagnosed in 3 patients (9.3%) and in 1 patient (4%) in Groups 1 and 2, respectively. The presence of nonunion was not statistically significant. (p=0.28)  Malunion was encountered in 2 patients (4%) in Group 2, while no patients experienced malunion in Groups 1 and 3. The presence of malunion was not statistically significant. (p=0.10)Conclusion: The EFA+TEN is a practical, safe and fast procedure providing a minimally invasive surgical treatment option for patients with humerus diaphysis fractures.
Keywords: Humerus; Fracture; Plate; External fixator; Nail